Quality culture in Tanzanian schools: A scoping Review - Revocatus C Kuluchumila; Ezra Nathanael Ntazoya (My University, 2025)
The present scoping research aimed to investigate how and the degree to which quality culture is embedded in Tanzanian schools. The search engines on quality culture came up with 39 published and unpublished sources. The reviewed sources revealed availability of education infrastructure to be one of key factors on improving quality culture in schools. The research results indicated further that improving the culture of community engagement could facilitate timely construction of classes. Results revealed also that, low commitment of teachers contributed to poor quality in education. Moreover, good teacher-students relationship was revealed as a significant factor on building the learning culture. Regarding the extent to which the linkage between the formal framework and human dynamics adds to building quality culture in schools, research findings indicated that, the community was deprived on engaging in various school activities to promote quality learning. Other research results indicated that majority of teachers lacked competence on integrating ICT in the teaching and learning process. Last but not least, school leadership to a greater degree lacked competence on building strong positive quality culture in their respective schools. It was generally revealed by reviewed studies that numerous elements of quality culture were embedded in Tanzanian schools.
Keywords: Quality culture; formal structures; human dynamics; school leadership; systematic review